Peran Katekis dalam Mengoptimalkan Analisa Sosial untuk Merancang Katekese Kontekstual yang Akurat - Jenny Fransisca Datu; Instansakti Pius X (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
Catechesis is the process of faith formation conducted by the Church to assist the faithful in understanding and living the Catholic faith. To design accurate contextual catechesis, catechists need to understand the needs and context of the society. In this regard, social analysis plays an important role in designing contextual catechesis. Social analysis is the process of collecting and analyzing data about society. This article focuses on the role of catechists in optimizing social analysis to design accurate contextual catechesis. The purpose of this article is to explain the role of catechists in optimizing social analysis, as well as the importance of social analysis for contextual catechesis. The issue in this article is how catechists can optimize social analysis to design accurate contextual catechesis. The implication of this study is that catechists need to have a good understanding of social analysis and how to optimize it in designing contextual catechesis. This article uses a qualitative research method with a literature study approach. The data used in this article is secondary data from various sources, such as books, articles, and journals. Based on the research results, it was found that catechists have an important role in optimizing social analysis to design accurate contextual catechesis. Social analysis is important in designing contextual catechesis because it can help catechists understand the needs and context of society, design relevant and effective catechesis, and improve the quality of catechesis.